Advances in the management of Drosophila suzukii population: from olfactory and visual stimuli to development of push–pull systems - Cruz-Esteban, Samuel (Frontiers in Ecology and Evolution, 2026)
Drosophila suzukii (Matsumura) is an invasive pest of major concern because of its ability to lay eggs in immature or thin-skinned ripening fruits, leading to substantial economic losses in berry production. This review examines recent advances in ethological control strategies—those that exploit pest behavior—including olfactory attractants, visual stimuli, trap density and spacing for mass trapping, and push–pull systems incorporating oviposition deterrents. Original data from Mexico and other countries are included, along with a discussion of current limitations, knowledge gaps, and future research directions aimed at improving practical effectiveness.